Análise dos aspectos demográficos e socioambientais para elaboração de um Índice de Segregação Espacial Urbana. - Marcos Roberto Martines; Rúbia Gomes Morato; Fernando Shinji Kawakubo; Ricardo Vicente Ferreira; Rogério Hartung Toppa (Confins)
Urban spatial segregation in developing countries is related to the social and economic differences of its population. This study presents an index of urban spatial segregation based on socioenvironmental and demographic data and performs statistical tests to evaluate its consistency. The index is presented with values between 0 and 1, with the highest values indicative of greater urban spatial segregation, thematic classes were derived and mapped at the level of census tracts based on data from the Brazilian census of 2010 and from images of Sentinel 2A and 3 to the urban areas of Uberlândia. The result shows less segregation indices in the South and high indices in the Southeast, North and West portions of the urban spot. The variables of urban infrastructure, economic and demographic conditions explain the groupings of the less segregated classes, on the other hand, the more segregated classes are directly influenced by the income variable. It was concluded that the urban spot shows a behavior of urban segregation of the center-periphery model and that the developed index presented a pattern of consistency.